Tedizolid Population Pharmacokinetics, Exposure Response, and Target Attainment - Flanagan, S. (Antimicrob Agents Chemother, 2014)
Tedizolid phosphate is a novel antibacterial prodrug that is rapidly and extensively converted to its active moiety, tedizolid. We developed a population pharmacokinetics (PK) model for tedizolid using pooled data from seven densely and sparsely sampled clinical trials evaluating oral and intravenous tedizolid. Model-derived exposure estimates were evaluated for relationships to select efficacy and safety outcomes. A two-compartment model with sigmoidal absorption, absolute bioavailability, and linear elimination described the PK data well. Variability was small (clearance, 31% coefficient of variation; volume, 13.4% coefficient of variation), and absolute bioavailability was high (86%). No clinically significant covariate effects on tedizolid PK were found. Based on phase 3 data evaluating 200-mg once-daily tedizolid for acute bacterial skin and skin structure infections (ABSSSI), no relationships were seen between various efficacy outcomes and estimated tedizolid exposure; the estimated exposure range (free-drug area under the concentration-time curve over 24 h at steady state [AUC(ss(0–24))], 7 to 50 μg · h/ml) in these patients was modest. Safety data modeling, using once-daily doses of up to 400 mg, showed a small increase in the probability of an adverse event with increasing model-estimated tedizolid exposure; no such relationship was observed when specifically evaluating the 200-mg dose. There were no trends in neutrophil or platelet counts with increasing tedizolid exposure. Target attainment simulations for 200-mg tedizolid indicated a 98.31% probability of attaining the target measure (AUC for the free, unbound fraction of a drug [fAUC]/MIC = 3) against a Staphylococcus aureus strain for which the MIC was ≤0.5 μg/ml. These findings support 200-mg tedizolid once daily as the optimum dose for treatment of ABSSSI.